Analysis of the Implementation of Religious Morals in Literacy Activities in Elementary School - Ahmad Hariandi; Annisa Fitrah; Dheada Sakila; Ilham Ifliadi; Alken Irwan; Beno Adi Pratama (Elementary: Jurnal Ilmiah Pendidikan Dasar, 2020)
The research aimed to find out how to apply religious morals and literacy activities in elementary schools. This research used qualitative research methods with this type of concept analysis research. The data were collected through observation, interview and documentation, and then analyzed using Miles and Huberman techniques namely data reduction, data presentation, and conclusion withdrawal. The research procedure went through several stages, namely the preparation stage, the implementation stage, and the completion stage. The research was conducted in SD Negeri 13/I Muara Bulian. The result of this study showed that literacy activities conducted in the classroom were reading 15 minutes before learning and reading chapter Yasin routine every Friday. The activicty was effective enough to apply moral values especially religious morals to students if the book read contains many moral values in it.